Participatory crop improvement and formal release of Jethobudho rice landrace in Nepal - Gyaw, S.; Sthapit, B.R.; Bhandari, B.; Bajracharya, J.; Shrestha, P.K.; Upadhyay, Madhusudan P.; Jarvis, Devra I. (Springer, 2010)
Jethobudho is an aromatic rice landrace of the Pokhara valley in middle hills of Nepal. Although local consumers are willing to pay a high price for its purchase, the landrace has a problem with quality variation. Decentralized participatory population improvement for specific market-identified traits was conducted on ‘‘Jethobudho’’ populations collected from farmers’ fields in seven geographic regions of the valley in Nepal. The preferred post harvest quality traits, field tolerance to blast and lodging, and superior post harvest quality traits of Jethobudho were established by a consumer market survey. These traits were used for screening the materials. 338 sub-populations of Jethobudho were evaluated for yield, disease, lodging resistance, and post harvest quality traits. Significant variation was found for culm strength, neck blast tolerance, awn characteristics, panicle length, number of grains per panicle, test grain weight and post harvest quality traits, whereas no significant variation was found in grain yield, plant height, tiller number, maturity period and leaf blast. Based on these identified traits and micro-milling evaluations, 183 populations were screened in on-farm and on-station nurseries, and in succeeding years populations were further screened by plant breeders and expert farmers in research trials, resulting in the selection of 46 populations for post harvest quality traits. Six accessions with similar agronomic traits, field tolerance to blast and lodging, and superior post harvest quality traits, were bulked and evaluated on-farm using participatory variety selection (PVS). The enhanced Jethobudho accessions were also evaluated for aroma using simple sequence repeat (SSR) and found to have unique aromatic genetic constitution. Community based seed production groups were formed, linked to the Nepal District Self Seed Sufficiency Programme (DISSPRO), and trained to produce basic seeds (truthfully labeled) of Jethobudho. The National Seed Board of Nepal released the enhanced landrace in the name of ‘‘Pokhareli Jethobudho’’ in 2006, as the first bulk variety of traditional high quality aromatic rice improved through articipatory plant breeding to be formally released in Nepal for general cultivation under the national seed certification scheme. Landrace improvement is shown as an important option for supporting programmes for in situ conservation of landraces on-farm.